The recruit : the graphic novel - Edginton, Ian.; Aggs, John.; Muchamore, Robert (London : Hodder Children's, 2012)
A terrorist doesn't let strangers into her flat because they might be undercover police or intelligence agents, but her children bring their mates home and they run all over the place. The terrorist doesn't know that one of these kids has bugged every room in her house, made copies of all her computer files and stolen her address book.
Formerly CIP.
Keywords: CHERUB (Imaginary organization) -- Comic books, strips, etc; Young adult fiction; Graphic novels